2023
DOI: 10.3390/app13095421
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Deep Learning-Based Damage Identification Approach for SHM Considering Missing Data

Abstract: Data-driven methods have shown promising results in structural health monitoring (SHM) applications. However, most of these approaches rely on the ideal dataset assumption and do not account for missing data, which can significantly impact their real-world performance. Missing data is a frequently encountered issue in time series data, which hinders standardized data mining and downstream tasks such as damage identification and condition assessment. While imputation approaches based on spatiotemporal relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…To avoid structural failure and severe loss, it is necessary to quickly detect damage in composite structures to prolong their service life. PHM technology provides early damage detection and helps avoid the deterioration of various industrial systems [7][8][9][10][11][12]. Recently, techniques for PHM based on Machine Learning (ML) and Deep Learning (DL) using vibration signals have been continuously adopted for fault diagnosis in various structures.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid structural failure and severe loss, it is necessary to quickly detect damage in composite structures to prolong their service life. PHM technology provides early damage detection and helps avoid the deterioration of various industrial systems [7][8][9][10][11][12]. Recently, techniques for PHM based on Machine Learning (ML) and Deep Learning (DL) using vibration signals have been continuously adopted for fault diagnosis in various structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, as the collected data usually consist of sequential time series signals, the most efficient deep learning architecture to be applied for prediction and classification falls within the RNNs domain [24]. In particular, it has been demonstrated that the advanced sub-class named Long Short-Term Memory (LSTM) networks [25,26] yields superior results when analysing and classifying time series without the need for complex preprocessing and hand-crafted feature extraction [27]. This paper introduces an LSTM architecture to investigate structural health monitoring for space systems, given its relatively new application to this sector.…”
Section: Introductionmentioning
confidence: 99%
“…Data normalisation: This step is crucial to ensure the data are in the proper range of the dynamic variability in the learning space of the DL network. It was proven [25] that, for this type of application, normalisation with respect to the mean and standard deviation of samples offers better results than minimum-maximum processing.…”
mentioning
confidence: 99%
“…In recent years, the establishment of an efficient health monitoring system capable of accurately detecting internal signals from civil structures has emerged as a prominent concern in the field of civil engineering [1][2][3][4]. In the structural health monitoring system (SHMS), classical on-site measurement methods such as ambient vibration testing [5], forced vibration testing [6], and impact vibration testing [7], which are direct methods, often require the installation of numerous sensors directly on the bridge structure [8,9], and the selection of a vibration parameter that is sensitive to structural damage (e.g., frequency [10], mode shape [11], strain energy [12], etc.…”
Section: Introductionmentioning
confidence: 99%